Assessment of imaging, pathoanatomy and terminology in posterior tibial tendon dysfunction - Workman, Matthew; Saragas, Nick; Ferrao, Paulo (Journal of the Foot & Ankle, 2020)
Objective: This study aimed to determine damage/change occurring in the posterior tibial tendon of patients undergoing surgery for posterior tibial tendon dysfunction (PTTD) and to correlate preoperative imaging and intraoperative findings with histology to determine the most appropriate investigations for diagnosis. The secondary aim was to clarify terminology used in describing the tendon pathology, to improve descriptive terminology for research, assessment, and treatment of PTTD. Methods: The records of patients who had undergone surgery for stage 2 PTTD were retrospectively reviewed. Cases in which preoperative diagnostic imaging was done and a posterior tibial tendon specimen was sent for histology were included. Ultrasound (US) and MRI findings, surgical notes and histopathological reports were evaluated. Results: Nineteen patients met the inclusion criteria. Fourteen had US showing degenerative changes and synovitis. Five had MRI showing tendon degeneration, with rupture in two cases. Intraoperatively, all tendons showed gross abnormality, with surrounding synovitis. Microscopically, no acute inflammation was noted within any tendon specimens. All had non-specific reactive changes within the visceral synovium. Conclusion: This study confirms clear histological degeneration within the posterior tibial tendon of patients undergoing corrective surgery for PTTD. Preoperative imaging and surgical findings identified tendon sheath synovitis. Pre-operative ultrasound imaging and intraoperative confirmation of PTTD is accurate; thus, histological confirmation is unnecessary. The pathological changes in PTTD have been described as a tendinopathy in the literature. We suggest using the term pantendinopathy, which is a combination of peritendinitis with tendinosis, as it better describes the pathological process. Level of Evidence IV; Therapeutic Studies; Case Series